Inertial amplification induced band gaps in corrugated-core sandwich panels. (1st July 2021) - Xi, Chenyang; Dou, Lingling; Mi, Yongzhen; Zheng, Hui
Abstract: Corrugated-core sandwich panels (CSPs) have numerous applications but suffer from poor vibration performance in low-frequency range. To address this issue, a type of four-bar inertial amplification (IA) mechanism, whose inertia is increased by amplifying the movement of small masses, is proposed here to enhance the low-frequency vibration reduction capability of CSPs. The proposed structure is modelled by using finite element method (FEM) with considering the in-plane and out-of-plane degrees of freedom of IA mechanisms simultaneously. After validating the proposed model by the commercial software from the perspective of the band-structure, the vibration characteristics of the IA-CSP are investigated numerically. The results show that the attachment of the IA mechanisms can obtain wide bandgaps in low-frequency range, which hence greatly enhancing the vibration suppression performance of typical CSPs. Compared with the local resonators attached CSP, the proposed IA-CSP achieves broader band attenuation in low-frequency range with the same additional mass. Considering spatial constraints, the parametric studies are performed, which reveals that the spans and local stiffness of the IA attached locations determine the degree of nonlocality and hence influence the edge frequencies of bandgaps. The concept of tunable bandgap knob is finally presented to realize the dynamic manipulation of bandgaps under the spatial constraints.